Shouting at the rain - Hunt, Lynda Mullaly (Puffin Books, an imprint of Penguin Random House, 2019)
Summary: From the author of the New York Times bestseller Fish in a Tree comes a compelling story about perspective and learning to love the family you have. Delsie loves tracking the weather--lately, though, it seems the squalls are in her own life. She's always lived with her kindhearted Grammy, but now she's looking at their life with new eyes and wishing she could have a "regular family." Delsie observes other changes in the air, too--the most painful being a friend who's outgrown her. Luckily, she has neighbors with strong shoulders to support her, and Ronan, a new friend who is caring and courageous but also troubled by the losses he's endured. As Ronan and Delsie traipse around Cape Cod on their adventures, they both learn what it means to be angry versus sad, broken versus whole, and abandoned versus loved. And that, together,